Cisatracurium inhibits the proliferation, migration and invasion of breast cancer cells by regulating the expression of miR-3174 - Yang, Xiaozhong; Ma, Wenxia (Cellular and Molecular Biology, 2020)
Breast cancer is a type of cancer that begins in the breast tissue. Being a woman is the most important factor in the risk of breast cancer. Although men also get the cancer, women are much more likely to get it. This experiment was founded to investigate the effect and mechanism of Cisatracurium on breast cancer cell proliferation, migration and invasion. Breast cancer cells MDA-MB-231 were cultured in vitro. MDA-MB-231 cells were treated with cisatracurium of different concentrations for 48 h. CCK-8method detected cell proliferation, Transwell detected cell migration and invasion, Western Blot method detected the expression levels of CyclinD1, p21, MMP-2andMMP-9protein in cells, RT-qPCR) detected the expression level of miR-3174in cells. After miR-3174 inhibitor was transfected into MDA-MB-231 in order to down-regulate the expression of miR-3174, the same methods as above were used to observe the effect of the down-regulating miR-3174 expression on MDA-MB-231 cell proliferation, migration and invasion as well as the expression levels of CyclinD1, p21, MMP -2 andMMP-9 protein. After different concentrations of Cisatracurium acted on MDA-MB-231 cells, the cell inhibition rate and p21 protein expression were significantly increased (p<0.05), the number of cell migration and invasion and the expression levels of CyclinD1, MMP-2 and MMP-9 were significantly reduced (p<0.05), and the expression of miR-3174 in cells was significantly reduced (p<0.05). After down-regulating the expression of miR-3174, the cell inhibition rate and p21 protein expression were significantly increased (p<0.05), the number of cell migration and invasion and the expression levels of CyclinD1, MMP-2 and MMP-9 were significantly reduced (p<0.05). Up-regulating miR-3174 expression could reverse the effect of Cisatracurium on the proliferation, migration and invasion of MDA-MB-231 cells. Cisatracurium can inhibit the proliferation, migration and invasion of breast cancer MDA-MB-231 cells, and its mechanism is related to the down-regulation of miR-3174 expression in cells.